PENERAPAN METODE MIND MAPPING PADA PEMBELAJARAN PAI DI KELAS XI SMK KARYA GUNA 1 BEKASI - Merlin Diah Cahyani; Laela Apri Liani (Universitas Maritim AMNI Semarang, 2023)
This study discusses the application of the Mind Mapping method to PAI learning at SMK Karya Guna 1 Bekasi. The purpose of this study was to find out whether the application of the Mind Mapping method in PAI learning at SMK Karya Guna 1 Bekasi in Class XI was successful or not. The purpose of this research is to prove that by applying the Mind Mapping method to pie learning in schools. By applying the Mind Mapping method it can stimulate students to be active in class, and be able to discuss with peers, and also be able to solve problems by discussing. In this study it can be proven that one of the ways to arouse student activity is to use the Mind Mapping method in teaching PAI at school. Based on the results of this study, it can be seen that applying the Mind Mapping method to PAI learning at SMK Karya Guna 1 Bekasi is well implemented. This can be proven by the application of the Mind Mapping method to PAI learning at SMK Karya Guna 1 Bekasi. Using this method can produce active and critical students in dealing with problems, as well as being able to discuss and respect friends' opinions when discussing, increasing the level of independence in learning. Not only using the discussion method, the teacher must also provide motivation in learning so that students can learn optimally.